Selecting and Developing Professionals - Makmur Syukri; Amiruddin Siahaan; Sri Rahayu Nasution; Rija Ansyari (Universitas Muhammadiyah Enrekang, 2022)
This study aims to examine Selecting and Developing Professionals. The research method used is library research. In collecting data, the factual study method was used. The results of the research from selecting and developing professionals were allegations of a teacher supply crisis, teacher recruitment and selection, teacher induction, teacher development, teacher retention, leadership recruitment and selection and leadership preparation and induction. This factual review (analysis) section focuses on the selection and development of two groups of staff, namely teachers and school principals. Learning organizations are meant to be inclusive, so all staff should be selected and developed with equal care. However, human resources are limited and it is undeniable that some categories of staff tend to have a greater impact on student learning than others. Principals have a variety of structures available to them that reflect organizational interests as well as individual interests.